Identifying Barriers and Facilitators to the Improvement of Healthcare Delivery and Ethics in Two Cameroonian Neurosurgical Centers - Ankeambom, Tutuwan J.; Motah, Mathieu; Ewane, Mfouapon; Shlobin, Nathan A.; Mbangtang, Celestin Bilong; Dada, Olaoluwa Ezekiel; Kabulo, Kantenga Dieu Merci; Tetinou, Francklin; Endalle, Geneviève; Kanmounye, Ulrick Sidney; Jokonya, Luxwell; Esene, Ignatius N. (Frontiers in Surgery, 2022)
Background Low-and middle-income countries (LMICs) are disproportionately affected by neurosurgical burden of disease. This health inequity causes constraints in decision-making. Neurosurgical ethics helps us to assess the moral acceptability and effectiveness of clinical decisions. We aimed to assess ethical neurosurgical care and its effect on patient satisfaction in Cameroon. Methods Two questionnaires hosted on Google Forms were administered among inpatients and staff at two Cameroonian neurosurgery centers. The questionnaires covered the factors influencing health outcomes and ethics. Data were collected from November 11, 2020, to March 11, 2021 and analyzed with SPSS v 26 to generate non-parametric tests with a threshold of significance at 0.05. Results Seventy patients and twenty healthcare providers responded to the survey. Most patients faced financial hardship (57.1%; 95% CI = 45.7–68.6%), and felt that this affected the care they received (P = 0.02). Patients noticed changes in the care plan and care delivery attributable to the neurosurgical units' lack of resources. According to the patients and caregivers, these changes happened 31.0–50.0% of the time (42.9%, 95% CI = 5.7–21.4%). The majority of patients were pleased with their involvement in the decision-making process (58.6%; 95% CI = 47.1–70.0%) and felt their autonomy was respected (87.1%; 95% CI = 78.6–94.3%). Conclusion Multiple challenges to neurosurgical ethical care were seen in our study. Multimodal interventions based on the four ethical principles discussed are necessary to improve ethical neurosurgical decision-making in this low resource setting.